2022
DOI: 10.1002/jsfa.11893
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aroma‐active compounds responsible for the floral and sweet odors of Congou black teas using gas chromatography–mass spectrometry/olfactometry, odor activity value, and chemometrics

Abstract: BACKGROUND: Floral and sweet odors are two typical characteristic aromas of Congou black tea, but their aroma-active compounds are still unclear. Characterizing the key aroma-active compounds can provide a theoretical foundation for the practical aroma quality evaluation of Congou black tea and directional processing technology of high-quality black tea with floral or sweet odors. Gas chromatography-olfactometry (GC-O) combined with odor activity value (OAV) is often used to screen key aroma-active substances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…The odor activity value (OAV) was defined as the ratio of flavor substance concentration to its aroma threshold. The larger the OAV is, the higher the aroma contribution to the flavor of the base liquor [ 40 ]. Additionally, 14 kinds of flavor substances with higher OAV (>1.0) were comparatively analyzed as the key components of flavor in the base liquor ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The odor activity value (OAV) was defined as the ratio of flavor substance concentration to its aroma threshold. The larger the OAV is, the higher the aroma contribution to the flavor of the base liquor [ 40 ]. Additionally, 14 kinds of flavor substances with higher OAV (>1.0) were comparatively analyzed as the key components of flavor in the base liquor ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…An 8 mL diluted sample and 3 g NaCl was added into a 15 mL sample bottle, and 10 μL of 10 mg/L 2-octanol was added as internal standard. Solid phase microextraction (SPME) was carried out at 50 °C for 30 min before GC-MS analysis (Thermo, Shanghai, China) [ 40 ]. According to the ratio of the area of internal standard to the area of flavor substances, the relative concentration of flavor substances was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown the formation of key aroma substances contributing to black tea odor during the fermentation process [ 39 , 40 ]. In this process, the aroma precursors, including fatty acids (such as linolenic and linoleic), amino acids (such as phenylalanine and methionine), geranyl/farnesyl pyrophosphate and carotenoids (such as β-caroteneand lutein), are correspondingly converted into fatty acid-derived volatiles (FADV), amino acid-derived volatiles (AADVs), volatile terpenoids (VTs) and carotenoid-derived volatiles (CDVs).…”
Section: Resultsmentioning
confidence: 99%
“…VTs such as nerol, α-farnesene and linalool and its oxides act together as key active compounds to provide floral aromas to black tea [ 42 ], while β-cyclocitral, which is attributed to CDVs, provides fruity and faint scents to congou black tea. Based on the available reports, it can be found that substances such as linalool oxides and ionone can increase black tea floral aroma, and benzaldehyde and phenylacetaldehyde can increase its sweet aroma [ 40 ]. Combined with Table S2 , all these substances were found to be most abundant in the RH95 treatment, and despite not being recognized as essential fragrance chemicals, they still contributed to the presentation of black tea’s aroma.…”
Section: Resultsmentioning
confidence: 99%
“…The aroma of tea is determined by VOCs [ 62 ]. The composition of VOCs in white tea is very complex, and most of these compounds are odorless or have a weak odor, so they have little effect on the formation of white tea aroma.…”
Section: Resultsmentioning
confidence: 99%